Experiencias de trabajo docenteanálisis de caso en el CIBV TAMIA SISA de la comunidad Izacata del cantón Cayambe - Tutillo Lanchimba, Lourdes Erminia (2018)
It is a qualitative research work, whose main objective is to understand through the teachers' own voice how they understand their educational practice. The work is framed within narrative investigations, understanding the narrative as that which is narrated in a time and in a certain space and that accounts for a way in which we look at the world. This work is located within the framework of CIBV TAMIA SISA located in the community of Izacata, Cangahua parish, Cayambe Canton. Being a qualitative research, we used the in-depth interview to collect the information after which a framework of information analysis was established. In collecting the teaching narratives we focus on understanding how the teachers describe their history; Narratives that are built in the day to day with the children and the main objective is to know their lived experiences with the girls, children in the indigenous community. How to interpret "quality education" only with narration of teachers can organize methodology, share their knowledge, teaching, learning; This stories motivate us to future teachers who hope to practice our profession field school.